Monitoring of charmed and beauty quark distributions in proton at LHC - Lykasov, G. I. (Array, 2008)
Summary: A short review on charmed and beauty hadron production in the lepton deep inelastic scattering off proton, in proton-proton and proton-antiproton collisions at high energies is presented. It is shown that the existing theoretical and experimental information on charmed and beauty quark distributions in a proton is not satisfactory. A procedure to study these distributions at LHC energies is suggested.